CLINICAL FEATURES AND RISK FACTORS FOR SEVERE COMPLICATIONS IN PATIENTS WITH HEPATITIS A VIRUS INFECTION FROM KAMRUP DISTRICT OF ASSAM, INDIA - PRIYANKA KASHYAP; MANAB DEKA; SANGIT DUTTA; MORTEZA KORDAFSHARI; MAJID KHANDOUZI; NAMRATA KUMARI (International Journal of Pharma and Bio Sciences, 2016)
Viral hepatitis caused by hepatitis A virus (HAV) infection is a worldwide disease; is a self-limited disease which results in fulminant hepatitis and death in only a small proportion of patients (0.1-2.1%). This study analyzes the clinical severity in patients with acute HAV infection and investigates risk factors associated with two severe complications: prolonged cholestasis and fulminant hepatic failure.A total of 150 patients with an age ranging from 12-40 years were included in the study and were analyzed by age, sex, other hepatotropic viral infection, etc. The patients were selected on the basis of clinical investigation and biochemical profile including ALT, AST, PT (Prothrombin time), TB (Total Bilirubin), Total Protein. Age >30 years (p=1.00; OR= 6.6) was a risk factor for prolonged cholestasis and FHF. Peak PT (INR) ≥1.5 (p <0.0001; OR = 1.0) was a significant risk factor for prolonged cholestasis and FHF. Total Bilirubin, AST and ALT levels were not shown to be significant risk factors. Creatinine level was a risk factor (p=0.009; OR=1.0) for prolonged cholestasis and Fulminant hepatic failure FHF.